Sliding Mode Control and Modified SVM for Suppressing Circulating Currents in Parallel-Connected Inverters. Issue 9 (28th May 2018) - Zorig, Abdelmalik; Belkheiri, Mohammed; Barkat, Said; Rabhi, Abdelhamid; Blaabjerg, Frede
Abstract: Parallel operation of multi-inverters is an effective way to increase the power capacity and the reliability of power electronic systems. However, in parallel inverter operation, one of the most crucial problems is the zero-sequence circulating current (ZSCC). The ZSCC flows between parallel inverters, which results in current distortion, harmonic loss, unbalanced load sharing, and a decline in the overall system performance. In this paper, a sliding mode ZSCC controller for paralleled three-phase inverters is proposed. The suggested controller takes advantage of zero-vector redundancies to adjust their dwell time and cancel any voltage difference that can generate ZSCC between the paralleled inverters. The appropriate adjustment quantity is determined using a sliding mode controller, and as a result, a better ZSCC cancelation can be achieved at different operation conditions. Experimental results of two parallel inverters show the feasibility of the proposed ZSCC elimination method.